Emily Gayle: capstone - Gayle, Emily, artist (Colorado State University. Libraries, 2021)
The artist's statement: Naturalistic expressionism evolved from regional and experiential processes is illustrated in my printmaking developments. Each print considers material, method, concept, and visual design to create impressionable outcomes. Materials I employ may include ash or essential oils sourced from the state of Colorado. Lithographs assembled with the entire stone enhance the presence of the human connection to the earth. Visual designs I choose are dependent on the concept demonstrated and my recognized emotional state. Compositions often interpret the Poudre Canyon to recreate landscapes that have imprinted on me. Experiences I select translate through gestural abstract marks. Reproducing a moment in time repeatedly with printmaking allows me to share this intimate experience with others and honor the existence of patterns in the world. My documentations holistically explore my identity as an artist in relation to my vast environment.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: printmaking